TPL Inhibits the Invasion and Migration of Drug-Resistant Ovarian Cancer by Targeting the PI3K/AKT/NF-κB-Signaling Pathway to Inhibit the Polarization of M2 TAMs - Le, Fuyin; Yang, Lilan; Han, Yiwen; Zhong, Yanying; Zhan, Fuliang; Feng, Ying; Hu, Hui; Chen, Tingtao; Tan, Buzhen (Frontiers in Oncology, 2021)
Chemoresistance is the primary reason for the poor prognosis of patients with ovarian cancer, and the search for a novel drug treatment or adjuvant chemotherapy drug is an urgent need. The tumor microenvironment plays key role in the incidence and development of tumors. As one of the most important components of the tumor microenvironment, M2 tumor-associated macrophages are closely related to tumor migration, invasion, immunosuppressive phenotype and drug resistance. Many studies have confirmed that triptolide (TPL), one of the principal components of Tripterygium wilfordii, possesses broad-spectrum anti-tumor activity. The aims of this study were to determine whether TPL could inhibit the migration and invasion of A2780/DDP cells in vitro and in vivo by inhibiting the polarization of M2 tumor-associated macrophages (TAMs); to explore the mechanism(s) underlying TPL effects; and to investigate the influence of TPL on murine intestinal symbiotic microbiota. In vitro results showed that M2 macrophage supernatant slightly promoted the proliferation, invasion, and migration of A2780/DDP cells, which was reversed by TPL in a dose-dependent manner. Animal experiments showed that TPL, particularly TPL + cisplatin (DDP), significantly reduced the tumor burden, prolonged the life span of mice by inhibiting M2 macrophage polarization, and downregulated the levels of CD31 and CD206 (CD31 is the vascular marker and CD206 is the macrophage marker), the mechanism of which may be related to the inhibition of the PI3K/Akt/NF-κB signaling pathway. High-throughput sequencing results of the intestinal microbiota in nude mice illustrated that Akkermansia and Clostridium were upregulated by DDP and TPL respective. We also found that Lactobacillus and Akkermansia were downregulated by DDP combined with TPL. Our results highlight the importance of M2 TAMs in Epithelial Ovarian Cancer (EOC) migration ability, invasiveness, and resistance to DDP. We also preliminarily explored the mechanism governing the reversal of the polarization of M2 macrophages by TPL.